COMPARISON OF ANESTHETIC EFFECT OF PLAIN ROPIVACAINE VERSUS DEXMEDETOMIDINE AS AN ADJUVANT TO ROPIVACAINE IN USG-GUIDED SUPRACLAVICULAR BLOCK FOR UPPER LIMB SURGERIES - MANISH KUMAR; PUNEETPAL KAUR; GEETANJALI SINGHAL; SUMAN KUMARI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Perioperative pain management is very important to achieve patient satisfaction. The objectives of the current study were to compare the anesthetic effects of dexmedetomidine and plain ropivacaine as an adjuvant to ropivacaine for upper limb surgeries in the supraclavicular brachial plexus block in terms of hemodynamic responses, quality, onset, and duration of sensory and motor block, post-operative pain management and side effects/complications if any. Methods: Sixty adult patients scheduled for upper limb surgeries were randomized into Group A and Group B of 30 patients each. Patients in Group A received 0.5% Ropivacaine 20 mL+5 mL normal saline and Group B received 0.5% ropivacaine 20 mL+0.5 mL (50 μg) dexmedetomidine+4.5 mL normal saline. The primary objective of our study was to compare the groups in terms of quality of block, onset, and duration of sensory and motor block and post-operative pain management. The secondary objective was to compare the intraoperative hemodynamic changes and post-operative adverse effects. Results: Time taken in the onset of the sensory as well as motor block in both the groups was statistically significantly more in Group A compared to Group B. The duration of the sensory as well as the motor block was much higher in Group B compared to Group A with a statistically significant difference. The total duration of analgesia was slightly higher in Group A compared to Group B. The mean numerical rating scale was significantly lower in Group B compared to Group A at all-time intervals till 24 h. No major side effects were observed with study drugs. Conclusion: The study confirmed that dexmedetomidine as an adjuvant to ropivacaine in supraclavicular brachial plexus block hastens the onset of the sensory as well as motor block and prolongs the duration of the sensory as well as the motor block in the upper limb surgeries.